2012 5th International Symposium on Communications, Control and Signal Processing 2012
DOI: 10.1109/isccsp.2012.6217862
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic traffic flow in a hyperbolic network

Abstract: In this work we study the asymptotic traffic flow in Gromov's hyperbolic graphs. We prove that under certain mild hypotheses the traffic flow in a hyperbolic graph tends to pass through a finite set of highly congested nodes. These nodes are called the "core" of the graph. We provide a formal definition of the core in a very general context and we study the properties of this set for several graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…In the study of communication networks, the core is usually identified by the small dense part that carries out most traffic under shortest path routing [5,24]. It is quite natural to associate the concepts of the network's core and its center.…”
Section: Theoretical Background and Related Workmentioning
confidence: 99%
“…In the study of communication networks, the core is usually identified by the small dense part that carries out most traffic under shortest path routing [5,24]. It is quite natural to associate the concepts of the network's core and its center.…”
Section: Theoretical Background and Related Workmentioning
confidence: 99%
“…The asymptotic traffic flow in hyperbolic graphs has been studied in Baryshnikov and Tucci. 25 It shows that a vertex v belongs to the core if there exists a finite radius r such that the amount of the traffic that passes through the ball centered at v and with radius r behaves asymptotically as (n 2 ) as the number of vertices n grows to infinity. The existence of the core in large networks such as the Internet motivates researchers to embed the Internet distance metric in a hyperbolic space for distance estimation.…”
Section: Core-periphery and Network Centrality In Complex Networkmentioning
confidence: 99%
“…It was suggested by Baryshnikov and Tucci 25 and Narayan and Saniee 6 that the highly congested cores in many communication networks can be due to their hyperbolicity or negative curvature. Those cores are represented by vertices that belong to most shortest paths (shortest-path betweenness centrality) and (or) have minimum distances to all other vertices (eccentricity centrality).…”
Section: Core-periphery Models Based On D-hyperbolicitymentioning
confidence: 99%
“…As a byproduct, we showed that the probability of a node having a load l scales as 1/l^2 in such models, a point of controversy prior to our work. A formal proof of O(N^2) scaling of load in δ-hyperbolic networks was subsequently furnished in [3,4,5].…”
Section: Project Accomplishmentsmentioning
confidence: 99%